2011
DOI: 10.1186/1471-2407-11-424
|View full text |Cite
|
Sign up to set email alerts
|

Activating mutation in MET oncogene in familial colorectal cancer

Abstract: BackgroundIn developed countries, the lifetime risk of developing colorectal cancer (CRC) is 5%, and it is the second leading cause of death from cancer. The presence of family history is a well established risk factor with 25-35% of CRCs attributable to inherited and/or familial factors. The highly penetrant inherited colon cancer syndromes account for approximately 5%, leaving greater than 20% without clear genetic definition. Familial colorectal cancer has been linked to chromosome 7q31 by multiple affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 26 publications
2
33
0
1
Order By: Relevance
“…After the discovery of MET mutations in HRPC, studies in other solid tumors identified MET kinase domain mutations and some mutations outside the kinase domain in childhood hepatocellular carcinomas, breast cancer, colorectal cancer (CRC), head and neck squamous cell cancers (HNSCC), gastric carcinomas (GC), and cancers of unknown primary origin (CUP) (Figure 1) (13)(14)(15)(16)(17)(18)(19)(20)(21). For several years after the initial discovery, the small number of MET kinase activating mutations identified in other carcinomas suggested that mutations within the MET kinase domain were rare events in cancer.…”
Section: Met Kinase Domain Mutations In Hereditary Papillary Renal Camentioning
confidence: 99%
“…After the discovery of MET mutations in HRPC, studies in other solid tumors identified MET kinase domain mutations and some mutations outside the kinase domain in childhood hepatocellular carcinomas, breast cancer, colorectal cancer (CRC), head and neck squamous cell cancers (HNSCC), gastric carcinomas (GC), and cancers of unknown primary origin (CUP) (Figure 1) (13)(14)(15)(16)(17)(18)(19)(20)(21). For several years after the initial discovery, the small number of MET kinase activating mutations identified in other carcinomas suggested that mutations within the MET kinase domain were rare events in cancer.…”
Section: Met Kinase Domain Mutations In Hereditary Papillary Renal Camentioning
confidence: 99%
“…MET mutations have been described in a variety of tumor types, spanning all domains of the MET gene. Both somatic and germline variants of MET have been reported in various human cancers, such as gastrointestinal malignancies [25,26]. In hereditary papillary renal cell cancer, TK domain gain-of-function mutations are demonstrated as oncogenic drivers.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, various Met mutations that lead to a constitutively activation of the receptor were described and many of them are located in the juxtamembrane [196] and in the kinase [195] domain. In recent studies it was shown that Met point mutations in non hereditary CRC are rare events [197,198]. The high Met expression observed in colorectal tumors and liver metastases is more frequently induced by genomic amplifications of the Met gene [199].…”
Section: The Hgf/met Pathway In Cancer and Crc Metastasismentioning
confidence: 99%